Compliance to antihypertensive medication: a cross-sectional study in Aligarh - Khwaja, Mariyam; Ansari, M. Athar; Mehnaz, Saira (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is a global public health issue. Hypertensive heart disease is one of the top ten leading causes of death in the world. It was responsible for an estimated 1.1 million deaths worldwide in 2012. To prevent some of the complications of hypertension regular intake of the prescribed treatment in the form of medicines (pills) is essential. Poor compliance to anti-hypertensive therapy is usually associated with bad outcome of the disease and wastage of limited health care resources. With these viewpoints the study aimed to assess the level of compliance of hypertensive patients to their anti-hypertensive medications and to determine the socio-demographic correlates of compliance. Methods: This was community based cross sectional study conducted in urban and rural areas in Aligarh. A total of 350 hypertensive patients were selected using simple random sampling. A pretested semi-structured questionnaire was used. Compliance was measured by Morisky 8-item Medication Adherence scale. Analysis was done using proportions and Chi-square test. Results: The overall compliance of study population was 23.7%. It was found to be significantly associated with gender, education, social class and associated co morbidities. Education, higher social class and duration of hypertension were found to be the main facilitators to adherence. The barriers to adherence were cost of drug and more number of pills per day. Conclusions: Patient education, family counselling and social support networks should be strengthened in health promotion programs in order to enhance compliance of hypertensive patients with the therapeutic regimen and to improve their quality of life.